Factors Affecting Corruption in Indonesia: Study on Local Government in Indonesia - Aris Eddy Sarwono; Rahmawati Rahmawati; Y. Anni Aryani; Agung Nur Probohudono (Universitas Pasundan, 2018)
This study aims to examine the factors that affecting corruption in Indonesia local governments. The sample used in this study consist of 225 Indonesian local governments. This study uses secondary data obtained from the Financial Audit Board (BPK) and Provincial Government’s Financial Report (LKPD) from 2010-2014 period along with composition data that's obtained from the Regional House of Representatives (DPRD) in Indonesia. Data analysis were performed using regression analysis. The results of the analysis show that corporate governance proxied with the composition of DPRDs that do not coalesce with the government, compared with the total DPRD has a significant effect on the corruption of local governments in Indonesia. The results of the analysis also show that the Regional Financial Information System (SIKD) has no effect on the corruption of local government. The control variables used in this study include the government's internal control system (weaknesses of accounting and reporting controls, weaknesses of controlling the execution of the budget and the weakness of the internal control structure) and the characteristics of local government (size of local government, asset, and balanced funds).